NARASI FILSAFAT KONTEMPORER MOHAMMAD ARKOUN (Dari Post-strukturalis Menunuju Kritik atas Nalar Islam) - Ismet Sari (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2019)
This paper explores the idea of Muhammad Arkoun who seeks to criticize the reasoning of classical Islam. Thought Arkoun is affected by movement (post) structuralist French. Arkoun historicism method used is the formulation of the social sciences inventions of modern Western thinkers (post) structuralist French. The main reference is De Sausure (linguistics), Levi Strauss (anthropology), Lacan (psychology), Barthes (semiology), Foucault (epistemology), Derrida (grammatologi), French philosopher Paul Ricour, anthropologists such as Jack Goody and Pierre Bourdieu. Arkoun borrows many concepts of the (post) structuralism for later introduction into the area of Islamic studies. Concepts such as corpus, Epistema, discourse, deconstruction, myth, logocentrism, the pitch, and not thought out, parole, aktant and others, is proof that Arkoun was brought up in an arena of struggle with (post) structuralism.